The dilemma in management of desmoid tumour: A case report - Fei, Yee Lee; Arvind Vashdev Jagwani; Mohamad Fairuz Mohamad Sharin; Andee Dzulkarnain Zakaria; Mohd Firdaus Mohd Hayati; Ismail Sagap (Collegium Medicum University of Warmia and Mazury, 2022)
Introduction: Desmoid tumours are rare benign tumours. The tumours may develop sporadically or they may be linked to familial adenomatous polyposis (FAP) in Gardner’s syndrome. Aim: This article highlights a young lady with an intra-abdominal desmoid tumour that manifested as an acute abdomen and we discuss our management strategy. Case study: A 24-year-old lady with a known FAP who had undergone a pan A 24-year-old lady with a known FAP who had undergone a panproctocolectomy with an ileal pouch-anal anastomosis and total thyroidectomy, later was complicated with acute abdomen for symptomatic desmoid tumour. Computed tomography of the abdomen showed a large intraperitoneal heterogenous mass with small bowel displacement and was confirmed by magnetic resonance imaging. An exploratory laparotomy and en-bloc resection of the tumour with an end ileostomy were performed. Results and discussion: Intra-abdominal desmoid tumours usually pre Intra-abdominal desmoid tumours usually present as a painless slow-growing mass, however, in severe form, it can cause bowel ischemia, intestinal obstruction, or deterioration of function in the ileoanal anastomosis, among post total colectomy. Surgery is indicated upfront in specific clinical scenarios namely complications (occlusion, perforation, or bleeding) or major cosmetic issues. Conclusions: Desmoid tumour, despite being benign, is challenging to manage due to its compressing nature. As a key point, the diagnosis of a desmoid tumour should be suspected and followed up closely in patients with a previous history of FAP in combination with extracolonic manifestation.